Surgical method and extent of reoperation in patients with concomitant strabismus - Xiao-Hua Xie (Guoji Yanke Zazhi, 2016)
AIM:To investigate the surgical method and extent of reoperation in the concomitant strabismus patients with surgical under-correction and over-correction. METHODS: Ninety-six concomitant strabismus patients with surgical under-correction and over-correction were recruited in this study, which included 41 males and 55 females, aged 21.90±14.70. All individuals underwent routine eye examinations for strabismus before the surgery. Among the cases with concomitant esotropia, there were over-correction in 23 cases, under-correction in 15 cases. Among the cases with concomitant exotropia, there were over-correction in 28 cases, under-correction in 30 cases. The method of reoperation were based on angle of deviation, the method of original operation and acute visual acuity of patients. RESULTS:In over-correction cases with concomitant esotropia,medial rectus muscle of 9 cases were advanced, the corrective extent was(5.51±2.63)△/mm; 9 cases were performed advance of medial rectus muscle and recession of lateral rectus muscle, the corrective extent was(6.25±1.59)△/mm; 3 cases were performed resection of medial rectus muscle and recession of lateral rectus muscle, the corrective extent was(4.26±1.04)△/mm; only 2 cases were performed recession of lateral rectus muscle, the corrective extent was(4.21±1.91)△/mm. In under-correction cases with concomitant esotropia, 6 cases were performed resection of lateral rectus muscle, the corrective extent was(4.03±0.98)△/mm; 6 cases were performed resection of lateral rectus muscle and recession of medial rectus muscle, the corrective extent was(6.86±1.32)△/mm; 3 cases were performed recession of medial rectus muscle, the corrective extent was(4.33±0.29)△/mm. In over-correction cases with concomitant exotropia, 16 cases were performed advance of lateral rectus muscle, the corrective extent was(5.37±1.56)△/mm; 6 cases were performed recession of medial rectus muscle, the corrective extent was(6.29±3.68)△/mm; 5 cases were performed advance of lateral rectus muscle and recession of medial rectus muscle, the corrective extent was(5.46±1.78)△/mm; 1 case were performed resection of lateral rectus muscle, the corrective extent was 5.00△/mm. In under-correction cases with concomitant exotropia, 12 cases were performed resection of medial rectus muscle, the corrective extent was(4.47±0.54)△/mm; 16 cases were performed recession of lateral rectus muscle and resection of medial rectus muscle, the corrective extent was(5.11±0.75)△/mm; 2 cases were performed recession of lateral rectus muscle, the corrective extent was(2.65±0.42)△/mm. CONCLUSION:In reoperation of concomitant strabismus patients with over-correction, weakening or/and strengthening the horizontal muscle which were performed surgery before has a greater and more unstable surgical corrective extent. While In reoperation of concomitant strabismuspatients with under-correction, weakening or/and strengthening the horizontal muscle which were not performed surgery has a normal corrective extent as usual.